2017
DOI: 10.1186/s12885-017-3199-3
|View full text |Cite
|
Sign up to set email alerts
|

Follicular thyroid carcinoma metastasis to the facial skeleton: a systematic review

Abstract: BackgroundFollicular thyroid carcinoma (FTC) metastasis to the facial skeleton is exceedingly rare. A case of FTC metastasizing to the mandible is presented and a systematic review of the literature describing thyroid metastasis to the facial skeleton is performed.Case presentationA 73-year-old female presented with metastatic FTC to the mandible and underwent total thyroidectomy, segmental mandibulectomy, bone impacted fibular free flap reconstruction, and adjuvant radioactive iodine treatment. The PubMed dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 58 publications
1
18
0
3
Order By: Relevance
“… 27 Varadarajan VV et al have also described facial skeletal metastasis of FC. 28 We also established a case of FC with bony metastasis in the left proximal arm in a 35 years old female. We had 2(2.02%) cases of medullary carcinoma thyroid in our current research which was similar to that presented by Singh SR & Iyengar S, Fatima A et al and Beigh A et al with 2 (2.5%), 8 (3.92%) and 1 (5%) cases respectively.…”
Section: Discussionmentioning
confidence: 97%
“… 27 Varadarajan VV et al have also described facial skeletal metastasis of FC. 28 We also established a case of FC with bony metastasis in the left proximal arm in a 35 years old female. We had 2(2.02%) cases of medullary carcinoma thyroid in our current research which was similar to that presented by Singh SR & Iyengar S, Fatima A et al and Beigh A et al with 2 (2.5%), 8 (3.92%) and 1 (5%) cases respectively.…”
Section: Discussionmentioning
confidence: 97%
“…[ 6 ] In the article by Varadarajan et al ., the authors summarized 41 reported cases in the literature of thyroid malignancy with metastasis to the mandible, of which 21 reported cases were FTC and from six reported cases of metastasis to the maxilla, two were FTC. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in a systematic review literature of 59 cases of thyroid cancer with facial skeleton metastasis, the overall survival rate was 96% at 2 years and 59% at 5 years. Among them, 22 cases were treated with surgery and postoperative radioactive iodine, yielding a survival rate of 100% at 2 years and 71% at 5 years16.…”
Section: Discussionmentioning
confidence: 99%